Taxonomic problems in Agathocles (Hemiptera: Heteroptera: Pentatomidae) with description of a new species - Rédei, Dávid; Tsai, Jing-Fu (Zootaxa, 2026)
Agathocles par sp. nov. (Hemiptera: Heteroptera: Pentatomidae: Pentatominae: Caystrini) is described from Yunnan, China. The new species is highly similar to A. limbatus Stål, 1876 externally. Problems with the identification of A. limbatus are highlighted, and the identity of this species is fixed by designating a neotype.